Մասնագիտական կրթության սոցիալական ուղղվածության հիմնախնդիրները - Նոննա Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
За десять лет Болонского процесса в системе профессионального образования в РА достигнуты серьезные результаты. Тем не менее, процесс реформирования по-прежнему не охватывает глубинные свойства, целенаправленные на обеспечение качественного профессионального образования. В статье представлены пути образовательных реформ по цепочке “старшая школа - бакалавр - магистратура- аспирантура”. The professional educational system organized in Armenia has secured serious results during the ten-year membership in the Bologna. Nevertheless, the reform process is not considering deep-rooted properties that would secure quality vocational education. This article considers certain reform methods in the High school, Bachelor, Masters and Doctorates educational cycles, that have a social significance as well.
Keywords: Theory and practice of education; Higher Education